Intracellular Alpha-Synuclein and Immune Cell Function - Grozdanov, Veselin; Danzer, Karin M. (Frontiers in Cell and Developmental Biology, 2020)
Intracellular alpha-synuclein has numerous effects on different functions of the cell. Although it is expressed in a wide spectrum of cell types from different lineages, most of our knowledge about it was generated by studying neuronal or glial cells. However, the role of immune cells in Parkinson’s disease and related synucleinopathies has recently emerged. Altered immune cell phenotypes and functions have been reported not only in animal models, but also in human disease. While the effects of extracellular alpha-synuclein on immune cells have been thoroughly studied, insights into the effects of intracellular alpha-synuclein on the function of immune cells remain scarce. Such insights may prove to be important for understanding the complex cellular and molecular events resulting in neurodegeneration and aid the development of novel therapies. We review the current state of knowledge about how alpha-synuclein and its pathologic manifestations affect the phenotype and function of peripheral and central nervous system immune cells, and discuss the potential of this topic for advancing our understanding of synucleinopathies.